2020
DOI: 10.3390/molecules25020420
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Olive Oil Stability Using Filtration and High Hydrostatic Pressure

Abstract: Veiled extra virgin olive oil (VEVOO) is very attractive on the global market. A study was performed to highlight the role of different amounts of water and microorganisms on the evolution of VEVOO quality during storage, using the selective effects of the application of individual or combined filtration and high hydrostatic pressure (HHP) treatments. Four oil processing trials were carried out in four replicates, resulting in a full factorial design with two independent fixed factors: filtration and HPP treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 43 publications
(66 reference statements)
5
26
0
Order By: Relevance
“…The turbidity fell from 2642 ± 174 NTU to 18 ± 4 NTU, and the water activity (aw) decreased from 0.70 ± 0.03 to 0.42 ± 0.04. These results are also consistent with the literature [11,22,26] regarding aw values and the turbidity grade of filtered oil.…”
Section: Turbidity Characterisation Microbial Contamination and Legsupporting
confidence: 93%
See 2 more Smart Citations
“…The turbidity fell from 2642 ± 174 NTU to 18 ± 4 NTU, and the water activity (aw) decreased from 0.70 ± 0.03 to 0.42 ± 0.04. These results are also consistent with the literature [11,22,26] regarding aw values and the turbidity grade of filtered oil.…”
Section: Turbidity Characterisation Microbial Contamination and Legsupporting
confidence: 93%
“…The latter is a combination of microdroplets of vegetation water and insoluble fruit solids, which are responsible for a wide spectrum of "turbidities" [20][21][22]. Veiled olive oils are rich in microflora, notably yeasts of candida species [11,16,[22][23][24][25]. The presence of these solid particles, which are rich in sugars, proteins, and water droplets, is associated with high water activity (greater than 0.6) [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ciafardini and Zullo [9] reported that low water content, which was observed in the EVOO derived from Leccino variety, prevents the deterioration of EVOO quality. Other studies have reported that high water content can adversely affect the shelf life of the product [12].…”
Section: Physicochemical Analysis Of the Monovarietal Evoos Used For mentioning
confidence: 96%
“…However, the sensory attributes of EVOO containing specific C. diddensiae yeast strains do not deteriorate even after four months of storage [10]. Yeast population density, strain, and enzymatic activity are reported to determine EVOO chemical composition [11,12]. However, the chemical composition of EVOO can influence the survival of some yeast species during storage [13].…”
Section: Introductionmentioning
confidence: 99%